Green synthesis, structure optimization and biological evalution of Rhopaladins’ analog 2–styryl–5-oxopyrrolidine-2- carboxamide RPDPRH on CaSki cells - Ke, Li-Na; Kong, Ling-Qi; Zhu, Xiu-Lian; Wu, Feng-Xu; Chen, Qin-Hua; Li, Bin; Dong, Yun; Wang, Hong-Mei; Zeng, Xiao-Hua (Frontiers in Chemistry, 2022)
We have synthesized Rhopaladins’ analog (2E,4E)-4-chlorobenzylidene-2-(4-chlorostyryl)-N-cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide (RPDPRH) via a highly facile, inexpensive and green approach and verified the structural superiority of compound RPDPRH through molecular docking. Moreover, we further detected the anti-proliferation, apoptosis and HPV E6/E7 effects of RPDPRH on CaSki cells. Finally, we confirmed that compared with the previous compound (E)-N-(tert-butyl)-2-(4-chlorobenzoyl)-4-(4-fluorobenzylidene)-1-isopropyl-5-oxopyrrolidine-2-carboxamide (RPDPB), RPDPRH could better inhibit proliferation, induce apoptosis, and down-regulate HPV E6/E7 mRNA expression on Caski cells. And preliminary RT-PCR experiments have demonstrated that RPDPRH also could affect the expression of Bcl-2, Bax and Caspase-3 mRNA in Caski cells. In summary, RPDPRH has potential as an effective agent against cervical cancer and will play an important role in our subsequent research.